CYANOACRYLATE INJURY TO THE EAR CANAL - Khan, Assad; Neminathan, Sinthuja; Sonsale, Anita; Dezso, Attila (Journal of Ayub Medical College Abbottabad, 2017)
This is a case regarding a 35-year-old gentleman who presented to the Accident and Emergency department at Walsall Manor Hospital. He had mistakenly placed cyanoacrylate ('˜superglue') into his right ear canal in the early morning. In terms of its removal, an initial attempt was made in the Ear, Nose and throat (ENT) outpatient clinic which proved to be unsuccessful due to the amount of discomfort it caused the patient. Therefore, it had to be removed under general anaesthesia. Keywords: Superglue; Cyanoacrylate; Walsall Manor Hospital